Storm surge-driven salinization mechanisms in coastal aquifers: Insights from 2D and 3D modelling in southwestern Bangladesh - ChiSan Tsai; Sean E. Feist; Mohammad A. Hoque; Kazi Matin Ahmed; Adrian P. Butler (Advances in Water Resources, 2026)

Insights on the heterogeneity of thermal transfer in the chalk aquifer using fibre-optic distributed temperature sensing - Katerina Kyrkou; Joseph Kelly; Adam Booth; Fleur Loveridge; David Boon; Edward Hough; Lawrence Scott; Matthew Jackson; Adrian Butler; Daniel Perez; Athena Chalari (Geothermics, 2026)

Tree shade protection factors by Jacaranda mimosifolia: a summertime comparison of UV dosimetry and whole sky image analysis for residential urban environments - Nathan J. Downs; Stijn Dekeyser; Adrian Dawes; Alfio V. Parisi; Harry J. Butler; Nawin Raj; Ravinesh C. Deo; Joanna Turner; Damien Igoe; Charlene Jackson; Catherine Chinnock; Melanie J. Beckman-Downs (Urban Forestry & Urban Greening, 2026)

Time-lapse resistivity imaging and self-potential monitoring of experimentally induced saline intrusion in coastal aquifer sands - Jesús F. Águila; Thomas S.L. Rowan; Mark C. McDonnell; Raymond Flynn; Shane Donohue; Matthew D. Jackson; Adrian P. Butler; Gerard A. Hamill; Eric M. Benner; Georgios Etsias (Science of The Total Environment, 2025)

Socio-hydrological modelling using participatory System Dynamics modelling for enhancing urban flood resilience through Blue-Green Infrastructure - Virginia Rosa Coletta; Alessandro Pagano; Nici Zimmermann; Michael Davies; Adrian Butler; Umberto Fratino; Raffaele Giordano; Irene Pluchinotta (Journal of Hydrology, 2024)

Dhaka city water logging hazards: area identification and vulnerability assessment through GIS-remote sensing techniques - Rafiul Alam; Zahidul Quayyum; Simon Moulds; Marzuka Ahmad Radia; Hasna Hena Sara; Md Tanvir Hasan; Adrian Butler (Environmental Monitoring and Assessment, 2023)
Water logging is one of the most detrimental phenomena continuing to burden Dhaka dwellers. This study aims to spatio-temporarily identify the water logging hazard zones within Dhaka Metropolitan area and assess the extent of their water logging susceptibility based on informal settlements, built-up areas, and demographical characteristics. The study utilizes integrated geographic information system (GIS)-remote sensing (RS) methods, using the Normalized Difference Vegetation Water and Moisture Index, distance buffer zone from drainage streams, and built-up distributions to identify waterlogged zones with a temporal extent, incorporating social and infrastructural attributes to evaluate water logging effects. These indicators were integrated into an overlay GIS method to measure the vulnerability level across Dhaka city areas. The findings reveal that south and south-western parts of Dhaka were more susceptible to water logging hazards. Almost 35% of Dhaka belongs to the high/very highly vulnerable zone. Greater number of slum households were found within high to very high water logging vulnerable zones and approximately 70% of them are poorly structured. The built-up areas were observed to be increased toward the northern part of Dhaka and were exposed to severe water logging issues. The overall findings reveal the spatio-temporal distribution of the water logging vulnerabilities across the city as well as its impact on the social indicators. An integrated approach is necessary for future development plans to mitigate the risk of water logging.

Fractal domain refinement of models simulating hydrological time series - Abrar Habib; Adrian P. Butler; John P. Bloomfield; James P. R. Sorensen (Hydrological Sciences Journal, 2022)

How groundwater time series and aquifer property data explain heterogeneity in the Permo-Triassic sandstone aquifers of the Eden Valley, Cumbria, UK - Alex Colyer; Adrian Butler; Denis Peach; Andrew Hughes (Hydrogeology Journal, 2022)
A novel investigation of the impact of meteorological and geological heterogeneity within the Permo-Triassic Sandstone aquifers of the River Eden catchment, Cumbria (UK), is described. Quantifying the impact of heterogeneity on the water cycle is increasingly important to sustainably manage water resources and minimise flood risk. Traditional investigations on heterogeneity at the catchment scale require a considerable amount of data, and this has led to the analysis of available time series to interpret the impact of heterogeneity. The current research integrated groundwater-level and meteorological time series in conjunction with aquifer property data at 11 borehole locations to quantify the impact of heterogeneity and inform the hydrogeological conceptual understanding. The study visually categorised and used seasonal trend decomposition by LOESS (STL) on 11 groundwater and meteorological time series. Decomposition components of the different time series were compared using variance ratios. Though the Eden catchment exhibits highly heterogeneous rainfall distribution, comparative analysis at borehole locations showed that (1) meteorological drivers at borehole locations are broadly homogeneous and (2) the meteorological drivers are not sufficient to generate the variation observed in the groundwater-level time series. Three distinct hydrogeological regimes were identified and shown to coincide with heterogeneous features in the southern Brockram facies, which is the northern silicified region of the Penrith Sandstone and the St Bees Sandstone. The use of STL analysis in combination with detailed aquifer property data is a low-impact insightful investigative tool that helps guide the development of hydrogeological conceptual models.

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Climate change and salinity in drinking water as a global problem: using remote-sensing methods to monitor surface water salinity - Yu Jeat Chong; Aneire Khan; Pauline Scheelbeek; Adrian Butler; David Bowers; Paolo Vineis (International Journal of Remote Sensing, 2014)

Soil organic carbon dust emission: an omitted global source of atmospheric CO 2 - Adrian Chappell; Nicholas P. Webb; Harry J. Butler; Craig L. Strong; Grant H. McTainsh; John F. Leys; Raphael A. Viscarra Rossel (Global Change Biology, 2013)
Soil erosion redistributes soil organic carbon ( SOC ) within terrestrial ecosystems, to the atmosphere and oceans. Dust export is an essential component of the carbon (C) and carbon dioxide ( CO 2 ) budget because wind erosion contributes to the C cycle by removing selectively SOC from vast areas and transporting C dust quickly offshore; augmenting the net loss of C from terrestrial systems. However, the contribution of wind erosion to rates of C release and sequestration is poorly understood. Here, we describe how SOC dust emission is omitted from national C accounting, is an underestimated source of CO 2 and may accelerate SOC decomposition. Similarly, long dust residence times in the unshielded atmospheric environment may considerably increase CO 2 emission. We developed a first approximation to SOC enrichment for a well‐established dust emission model and quantified SOC dust emission for Australia (5.83 Tg CO 2 ‐e yr −1 ) and Australian agricultural soils (0.4 Tg CO 2 ‐e yr −1 ). These amount to underestimates for CO 2 emissions of ≈10% from combined C pools in Australia (year = 2000), ≈5% from Australian Rangelands and ≈3% of Australian Agricultural Soils by Kyoto Accounting. Northern hemisphere countries with greater dust emission than Australia are also likely to have much larger SOC dust emission. Therefore, omission of SOC dust emission likely represents a considerable underestimate from those nations’ C accounts. We suggest that the omission of SOC dust emission from C cycling and C accounting is a significant global source of uncertainty. Tracing the fate of wind‐eroded SOC in the dust cycle is therefore essential to quantify the release of CO 2 from SOC dust to the atmosphere and the contribution of SOC deposition to downwind C sinks.

Evidence Supporting the use of Probiotics for the Prevention and Treatment of Chemotherapy-Induced Intestinal Mucositis - Luca D. Prisciandaro; Mark S. Geier; Ross N. Butler; Adrian G. Cummins; Gordon S. Howarth (Critical Reviews in Food Science and Nutrition, 2011)

Delineation of Source Protection Zones Using Statistical Methods - Fritz Stauffer; Alberto Guadagnini; Adrian Butler; Harrie-Jan Hendricks Franssen; Neeltje Van De Wiel; Mahmoud Bakr; Monica Riva; Laura Guadagnini (Water Resources Management, 2005)

Validation of quantitative trait loci for Ascochyta blight resistance in pea (Pisum sativum L.), using populations from two crosses - Gail M. Timmerman-Vaughan; Tonya J. Frew; Ruth Butler; Sarah Murray; Margy Gilpin; Karla Falloon; Paul Johnston; Michael B. Lakeman; Adrian Russell; Tanveer Khan (Theoretical and Applied Genetics, 2004)